Virtual reality for lecture halls and classroom in UTAR - Yu, Kar Hing (2023)
This project is to innovate the virtual reality classroom system to provide a new experience and raise an awareness of virtual reality classroom to users as it is yet a well-known platform in our country. Virtual classroom, a digital learning environment that allows teachers and students to connect via online in real time. Mostly, the virtual classroom that are commonly used among people is to make use of video conferencing, online whiteboards, share screens, etc. These features are performed to replace the physical actions. However, there are also some limitationssuch as lack of interactivity, lack of information provided, lack of focuses etc. Thus, this project will innovate the virtual reality classroom system by integrating special elements like selection of preferred avatar, tour around buildings, interesting and fun features inside the virtual space, etc into this project. This project is to aim to user interactions and improve their learning through this memorable and immersive experiences. Besides that, this project is designed to play in desktop or laptop platform due to budgets of a student. They might not have sufficient financial supports to buy a VR set. Therefore, this project provides equality to all the users to play and experience the virtual classroom.